2014
DOI: 10.1162/jocn_a_00654
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical Sentences Are More Emotionally Engaging than Their Literal Counterparts

Abstract: Why do people so often use metaphorical expressions when literal paraphrases are readily available? This study focuses on a comparison of metaphorical statements involving the source domain of taste (e.g., "She looked at him sweetly") and their literal paraphrases (e.g., "She looked at him kindly"). Metaphorical and literal sentences differed only in one word and were normed for length, familiarity, imageability, emotional valence, and arousal. Our findings indicate that conventional metaphorical expressions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
117
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(131 citation statements)
references
References 111 publications
12
117
0
2
Order By: Relevance
“…Since unambiguous idioms only possess a figurative interpretation, the fact that they are rated as more arousing and emotionally valenced than ambiguous idioms fits nicely with recent neuroimaging data showing that figurative formulations are more emotionally engaging than their literal counterparts (Citron & Goldberg, 2014).…”
Section: Ambiguous Versus Unambiguous Idiomssupporting
confidence: 79%
See 3 more Smart Citations
“…Since unambiguous idioms only possess a figurative interpretation, the fact that they are rated as more arousing and emotionally valenced than ambiguous idioms fits nicely with recent neuroimaging data showing that figurative formulations are more emotionally engaging than their literal counterparts (Citron & Goldberg, 2014).…”
Section: Ambiguous Versus Unambiguous Idiomssupporting
confidence: 79%
“…Recent brainimaging evidence has shown that nonliteral sentences evoked stronger implicit emotional responses than literal sentences (Bohrn, Altmann, & Jacobs, 2012). Similarly, a study on taste metaphors showed that metaphorical sentences elicited enhanced activation of the amygdala compared to their literal counterparts, which were matched for valence and arousal (Citron & Goldberg, 2014).…”
Section: Emotion and Figurative Languagementioning
confidence: 97%
See 2 more Smart Citations
“…A couple of fMRI studies have examined the link between metaphor and emotion (Bohrn et al, 2012;Citron and Goldberg, 2014). One example is an fMRI study by Citron and Goldberg (2014) in which participants read sentences with metaphorical content ('She looked at him sweetly') and carefully matched literal counterparts ('She looked at him kindly').…”
Section: Introductionmentioning
confidence: 99%